Bivalves límnicos invasores em uma planície aluvial Neotropical : invasibilidade e seus efeitos nas comunidades planctônicas. - Ragonha, Flávio Henrique (2015)
The species of bivalve Corbicula fluminea Müller, 1774 and invasive Limnoperna fortunei Dunker, 1857 are among the most invasive species that impact aquatic environments. Among its impacts are observed the disappearance of many native species due to competition for food. Filtration rates of these invasive species are high and influenced by several factors, among them, temperature, dissolved oxygen and turbidity. Therefore, was verified that the population dynamics and the pattern colonization of L. fortunei follows the same standards for floodplain, and what environmental factors are important for occurrence probability of the L. fortunei in the different size classes in different invaded environments. Besides, investigating the effect of predation of bivalve L. fortunei and C. fluminea on the phytoplankton and zooplankton at different levels of turbidity. In different age classes the requirements for environmental conditions showed change as the development stage. In younger age classes conditions with high turbidity values probably organic, total phosphorus and abundant oxygenation and high percentage of pebbles are the suitable setting for a higher probability of occurrence of this species. However, the individuals already established probably more tolerant the environmental changes need an environment where food, expressed by chlorophyll-a, is abundant to supply its high filtration rate. The differences in behavior in the capture of food can be a major explanation as to how these two species so different filtration rates can coexist in the same habitat, since even with a very high filtration rate L. fortunei in many situations the turbidity presented be less effective in capturing some zooplankton groups in relation the C. fluminea. The findings of the two studies expanded the knowledge of the ecology of these bivalve invaders supporting for future works.